2015
DOI: 10.1177/1362361314568899
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in pre-diagnosis concerns for children later diagnosed with autism spectrum disorder

Abstract: In the absence of intellectual impairment, girls are diagnosed with autism spectrum disorder significantly less and later than boys. This study explored potential reasons for why autism spectrum disorder may be more difficult to identify in girls, based on carer concerns during the pre-diagnosis period. Carers of 92 boys and 60 girls diagnosed with autism spectrum disorder from school age completed an online survey addressing concerns regarding the child's development during the pre-school years (pre-diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 18 publications
4
120
1
2
Order By: Relevance
“…(31) This could explain the observation in some studies that the ratio of boys to girls is about 4 at younger ages, but rises closer to 2 in late childhood and beyond. (4547) …”
Section: Discussionmentioning
confidence: 99%
“…(31) This could explain the observation in some studies that the ratio of boys to girls is about 4 at younger ages, but rises closer to 2 in late childhood and beyond. (4547) …”
Section: Discussionmentioning
confidence: 99%
“…In other words, the early signs of autism presented by females might be different from that of males, hence the diagnosis may vary even when controlling for certain variables such as IQ or age. This has been demonstrated in a study where early signs of autism before diagnosis were obtained from caregivers and compared between males and females who later went on to be diagnosed with autism (Hiller et al 2015). It was found that there are sex differences in several “core” autistic symptoms early on, in that females were more likely to engage in mimicking in social settings as well as displaying a stronger desire to interact with peers, which is in contrast to males who displayed social isolation.…”
Section: Sex Differences In Brain Disorders (Human Clinical Studies)mentioning
confidence: 97%
“…The application of this rote knowledge of social behavior may effectively hide an innate lack of skill in certain interactions, but the frequently monumental effort required to do this often goes unnoticed. In fact, though autistic females may have similar trouble with social communication as autistic boys do early in life, females may have greater social motivation and desire to be liked and engaged with her peers [62, 63]; this motivation may be what drives high functioning females in particular to camouflage their difficulties. It is unclear to what extent this desire and ability to compensate for social challenges by rote learning and performance of normative behaviors may be truly compensatory or protective against diagnosis in females, versus an exhausting and distressing burden for affected females to bear.…”
Section: Introductionmentioning
confidence: 99%